New public diplomacy and its effects on international level - Gurgu, Elena; Cociuban, Aristide Dumitru (Journal of Economic Development, Environment and People, 2016)
Abstract. The purpose of this article is to make known the new type of public diplomacy and the effects this new diplomacy can have internationally. The objectives of our article refer to the context of change, the role of the media in public diplomacy, new approaches and elements of public diplomacy, current diplomacy in scientific and technical way and the use of scientific cooperation to improve bilateral relations between countries.